Innovation aus Tradition : 175 Jahre KIT-Bibliothek - Scholze, Frank [Hrsg.] (KIT Scientific Publishing, 2015)
One of the most modern libraries in Germany today, the KIT Library of Karlsruhe Institute of Technology (KIT) already looks back on a 175-year long tradition. For the first time, this book combines a depiction of the evolution of the library of the ""Polytechnische Schule"" (polytechnic institute) to the university library in combination with the development of the ""Literaturabteilung"" (literature department) of the ""Forschungszentrum Karlsruhe"" (Karlsruhe Research Centre). From these historic roots has grown a high-performance service center for information and communication media. The present survey of the library history shows how innovation has become a tradition at KIT-Library.